Recipes and reciprocity : building relationships in research - Tait Neufeld, Hannah, 1968-; Finnis, Elizabeth, 1976- (University of Manitoba Press, 2022)
"Recipes as Reciprocity considers the ways that food and research intersect for both researchers, participants, and communities demonstrating how everyday acts around food preparation, consumption, and sharing can enable unexpected approaches to reciprocal research and fuel relationships across cultures, generations, spaces, and places. Drawing from research contexts within Canada, Cuba, India, Malawi, Nepal, Paraguay, and Japan, contributors use the sharing of food knowledge and food processes (such as drying, steaming, mixing, grinding, and churning) to examine topics like identity, community-based research ethics, food sovereignty, and nutrition. Each chapter highlights practical and experiential elements of fieldwork, incorporating storytelling, recipes, and methodological practices to offer insight into how food facilitates relationship-building and knowledge-sharing across geographical and cultural boarders. Contributors to this volume bring a range of disciplinary backgrounds--including anthropology, public health, social work, history, and rural studies--to the exploration of global and Indigenous foodways, perceptions around ethical eating and authenticity, language and food preparation, perspectives on healthy eating, and what it means to develop research relationships through food. Challenging colonial, heteropatriarchal, and methodological divisions between academic and less formal ways of knowing, Recipes as Reciprocity draws critical attention to the ways food can bridge disciplinary and lived experiences, propelling meaningful research and reciprocal relationships."--